American trade policy after the Kennedy Round - Harris P. Dawson (Intereconomics, 1967)
Not so long ago, Senator Dirksen, Republican, and his Democrat colleague, Senator Hartke, have placed before the US Senate a complete bunch of new restrictive bills on Imports, intending to cut all Imports by laying down reduced quotas. They were to shield all the branches of the US economy that have to compete keenly in the world's markets, against the impact of cheap foreign goods. These bills came not entirely surprising, as Immediately after the Kennedy Round a number of commentators were actuated by the fear lest the agreed tariff cuts should mobilise the protectionists in the US. INTERECONOMICS had occasion to talk about new problems of American trade policy with the Commercial Attaché Harris P. Dawson.
Keywords: 330; Interview